A concise in vitro model for evaluating interactions between macrophage and skeletal muscle cells during muscle regeneration - Kase, Naoya; Kitagawa, Yohko; Ikenaka, Akihiro; Niwa, Akira; Saito, Megumu K. (Frontiers in Cell and Developmental Biology, 2023)
Skeletal muscle has a highly regenerative capacity, but the detailed process is not fully understood. Several in vitro skeletal muscle regeneration models have been developed to elucidate this, all of which rely on specialized culture conditions that limit the accessibility and their application to many general experiments. Here, we established a concise in vitro skeletal muscle regeneration model using mouse primary cells. This model allows evaluation of skeletal muscle regeneration in two-dimensional culture system similar to a typical cell culture, showing a macrophage-dependent regenerative capacity, which is an important process in skeletal muscle regeneration. Based on the concept that this model could assess the contribution of macrophages of various phenotypes to skeletal muscle regeneration, we evaluated the effect of endotoxin pre-stimulation for inducing various changes in gene expression on macrophages and found that the contribution to skeletal muscle regeneration was significantly reduced. The gene expression patterns differed from those of naive macrophages, especially immediately after skeletal muscle injury, suggesting that the difference in responsiveness contributed to the difference in regenerative efficiency. Our findings provide a concise in vitro model that enables the evaluation of the contribution of individual cell types, such as macrophages and muscle stem cells, on skeletal muscle regeneration.